2015
DOI: 10.1093/jisesa/iev015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tithonia diversifolia Mulch on Atta cephalotes (Hymenoptera: Formicidae) Nests

Abstract: Recent studies have shown an insecticidal effect of Tithonia diversifolia (Hemsl.) Gray (Asterales: Asteraceae) foliage on workers of Atta cephalotes L. and inhibitory effects of this plant on the growth of the symbiotic fungus Leucoagaricus gongylophorus (A. Müler) Singer. To evaluate the potential of T. diversifolia as a biological control treatment of this important pest, we assessed the effect of green manure (mulch) of this plant on natural nests of A. cephalotes, in Cali, Colombia. Three treatments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
0
3
0
2
Order By: Relevance
“…(Osipitan & Oseyemi, 2012). Tithonia diversifolia juga dapat dimanfaatkan untuk mengendalikan Sitophilus zeamais (Onekutu et al, 2015) dan Atta cephalotes (Hymenoptera: Formicidae) (Zanetti et al, 2014, Rodriguez et al, 2015. Tithonia diversifolia diketahui mengandung beberapa senyawa metabolit sekunder diantaranya seskuiterpena, diterpena, monoterpena, dan kandungan alisiklik yang bersifat toksik yang berasal dari bagian daun, batang, atau bunga .…”
Section: Hasil Dan Pembahasanunclassified
“…(Osipitan & Oseyemi, 2012). Tithonia diversifolia juga dapat dimanfaatkan untuk mengendalikan Sitophilus zeamais (Onekutu et al, 2015) dan Atta cephalotes (Hymenoptera: Formicidae) (Zanetti et al, 2014, Rodriguez et al, 2015. Tithonia diversifolia diketahui mengandung beberapa senyawa metabolit sekunder diantaranya seskuiterpena, diterpena, monoterpena, dan kandungan alisiklik yang bersifat toksik yang berasal dari bagian daun, batang, atau bunga .…”
Section: Hasil Dan Pembahasanunclassified
“…Furthermore, ethanol extract from T. diversifolia dry leaves will produce 100% worker ant mortality in only eight days [10]. Recently, in a study conducted under natural conditions, Rodriguez et al [11] observed that green manure made with T. diversifolia will induce the displacement of the fungus-rearing chambers to deeper zones as well as the construction of new chambers outside the areas of manure degradation. Thus, due to its antifungal and insecticidal properties, the sunflower shows great potential for the control of leaf-cutter ants as well as other agricultural pests.…”
Section: Introductionmentioning
confidence: 99%
“…sobre o fungo Leocoagaricus gongylophorus. 16 Extratos de M. affinis foram testados sobre os fungos fitopatogênicos (Botryotinia fuckeliana, Magnaporthe oryzae, Phytophtora infestans e Septoria tritici). 17 A cultura do milho é de suma importância para a economia do Brasil, sendo este o terceiro maior produtor mundial.…”
Section: Introductionunclassified